A REPORT ON DIABETES AND RISK FOR CARDIOVASCULAR DISEASE - JANSIRANISIVA SUBRAMANIAN,; SHANKAR MANOHAR PAWAR,; E. PRABHAKAR REDDY,; ABIRAMI SOUNDARARAJAN,; HEMAVATHY RAMALINGAM, (The Bioscan, 2011)
Patients with diabetes mellitus are at high risk of cardiovascular disease and the risk is further increased when they are complicated with nephropathy, neuropathy or Retinopathy. 33 patients were recruited into the study (patient group) along with 33 healthy individuals (control group). The control group was recruited from the people attending the master health checkup program of the hospital and staff of the department. In the present study we have evaluated the diabetes and risk for CVD in rural population of India. We found increased fasting glucose and total cholesterol in test subjects compared to control, but these are statistically not significant. An increase in glucose and lipid profile they are well with in the normal range. But these finding are crucial because they are at the higher normal range. This could be due to due to small number of population and age factor of the participants. Further studies which include more number of subjects from rural area will through more light on Prevalence of diabetes and risk for cardiovascular disease.